2003
DOI: 10.1046/j.1440-1827.2003.01566.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD34 antigen in testicular mixed germ cell tumor

Abstract: The expression of CD34 was investigated in 14 cases of testicular mixed germ cell tumor to elucidate the relationship between its expression and histological patterns. Seven of 12 yolk sac tumor components were focally immunoreactive for anti-CD34 antibody. Of these, five showed focal but intense CD34 staining, while the remaining two tumors showed weak staining in small clusters or isolated tumor cells. Positive immunostaining for CD34 was seen predominantly in solid and reticular patterns of the yolk sac tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chou et al ( 9) previously reported on expression of CD34 in 5/15 prepubertal testicular GCT, all of which were YST, while no expression of this marker was found in 10 adult tumors consisting of different nonseminoma tumors. In contrast, Hamazaki and Okada (10) detected CD34 in 7/12 testicular YST, in a cohort in which all but one patient were adults. Our data are in agreement with the latter study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Chou et al ( 9) previously reported on expression of CD34 in 5/15 prepubertal testicular GCT, all of which were YST, while no expression of this marker was found in 10 adult tumors consisting of different nonseminoma tumors. In contrast, Hamazaki and Okada (10) detected CD34 in 7/12 testicular YST, in a cohort in which all but one patient were adults. Our data are in agreement with the latter study.…”
Section: Discussionmentioning
confidence: 78%
“…Expression of CD34 and CD44 has been reported in testicular GCT (9)(10)(11)(12), but has not, to the best of our knowledge, been studied in MOGCT. The current study analyzed the expression of these markers in a series of 49 tumors.…”
mentioning
confidence: 94%